2016
DOI: 10.1016/j.ihj.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, and control of hypertension in the slums of Kolkata

Abstract: There is a high prevalence of hypertension in the slums of Kolkata. Although the awareness of the condition is high, the control of hypertension is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 17 publications
9
37
2
1
Order By: Relevance
“…22 On the other hand there are studies which found smoking as significant correlate of hypertension. 23,24 Like the study done in India, our study also reveals that alcohol has no significant association with hypertension whereas other studies have reported that alcohol has significant association with hypertension. [24][25][26] There are studies demonstrating the positive relationship between alcohol use and hypertension.…”
Section: Discussionsupporting
confidence: 61%
“…22 On the other hand there are studies which found smoking as significant correlate of hypertension. 23,24 Like the study done in India, our study also reveals that alcohol has no significant association with hypertension whereas other studies have reported that alcohol has significant association with hypertension. [24][25][26] There are studies demonstrating the positive relationship between alcohol use and hypertension.…”
Section: Discussionsupporting
confidence: 61%
“…15 The differences may be attributed to the fact that the this previous study had both male and female participants. Tobacco use was found among 34% of all the male and female study participants in urban population 16 also which is similar to this rural population. Of the 31.6% of the females with the habit tobacco consumption, 61.2% have high BP.…”
Section: Discussionsupporting
confidence: 76%
“…A study in the year 2016 in the slums of Kolkata similarly concluded that only 30% of total 9088 study participants completed class X and 17% were illiterate. 16 Evidently those with higher education tends less towards high BP. Occupation leads to stressful conditions but here only 21% were working females rest were housewives.…”
Section: Discussionmentioning
confidence: 98%
“…A study carried out among 1154 adult populations in a municipal town of Kerala reported the prevalence of hypertension as 32.3% and also indicated that the prevalence increases with age [18]. A study carried out among 10,175 adults aged ≥20 years in slums of Kolkata reported the prevalence of hypertension as 42% and prevalence was higher in men, above 60 years age, in minority community, in those with a higher household income, and among tobacco users [19]. An epidemiological study carried out among 3629 adults between younger and older two age groups in western Indian population showed that hypertension prevalence differs in two different age groups 11% in younger (≤40 years)and 40% in older age groups (>40years) [20].…”
Section: Discussionmentioning
confidence: 99%